Crystal structure solution for the A6B2O17 (A = Zr, Hf; B = Nb, Ta) superstructure. Issue 2 (9th April 2019) - McCormack, Scott J.; Kriven, Waltraud M.
Abstract : The crystal structure solutions for Zr6 Ta2 O17, Hf6 Nb2 O17 and Hf6 Ta2 O17 have been solved using synchrotron X‐ray and neutron powder diffraction. These structures have been shown to be isomorphous with each other and Zr6 Nb2 O17, leading to the classification of the A 6 B 2 O17 orthorhombic compound family with symmetry Ima 2 (No. 46). Abstract : Zr6 Ta2 O17, Hf6 Nb2 O17 and Hf6 Ta2 O17 crystal structure solutions have been solved using synchrotron X‐ray powder diffraction and neutron powder diffraction in conjunction with simulated annealing, charge flipping and Rietveld refinement. These structures have been shown to be isomorphous with the Zr6 Nb2 O17 superstructure, leading to the classification of the A 6 B 2 O17 ( A = Zr, Hf; B = Nb, Ta) orthorhombic compound family with symmetry Ima 2 (No. 46). The asymmetrical structural units of cation‐centred oxygen polyhedra used to build the structure are as follows: (i) one set of symmetry‐equivalent six‐coordinated polyhedra, (ii) three sets of symmetry‐equivalent seven‐coordinated polyhedra and (iii) one set of symmetry‐equivalent eight‐coordinated polyhedra. The potential for cation order and disorder was discussed in terms of cation atomic number contrast in X‐ray and neutron powder diffraction as well as the bond valence method. In addition, the structural mechanisms for experimentally observed compositional variations within the solid solution range can be attributed to the addition or removal of a set of symmetry‐equivalent seven‐coordinated polyhedra accompanied by corresponding oxygen tilts within the A 6 B 2 O17 structure.